PENERAPAN MODEL PAIKEM GEMBROT UNTUK MENINGKATKAN KETERAMPILAN MEMBENTUK DARI BAHAN PLASTISIN PADA SISWAKELAS IVB SD NEGERI 56 PEKANBARU - Rossiana Victorius; Zariul Antosa; Hj. Munjiatun Hj. Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe research was done because it had never taught it in the form of clay material in SD Negeri 56 Pekanbaru . Still learning centered on learning drawing and drawing so that students are less skilled in the art and culture and learn other skills mainly formed of clay materials . The purpose of this research is to improve the skills of clay material in the form of fourth grade students of SD Negeri 56 Pekanbaru with the application of the model PAIKEM GEMBROTPlaydough fat in the subject matter . This research is a classroom action research Material covered , making homemade playdough , the practice of making crafts from clay with a floral theme , and the practice of making paper craft of clay with marine animal theme . The research subjects were students of SD Negeri 56 Pekanbaru IVB as many as 32 people . Instrument consists of : syllabi , lesson plan ( RPP ) , student worksheets , teacher observation sheet activities and student activities . Data analysis using descriptive analysis . The results showed an increase in the average value of the craft skills to make playdough from the base score to the first cycle , the second cycle to cycle and to III . Based on the research skills of students increased from baseline 41.87 ( unskilled category ) , after application of the model PAIKEM GEMBROT fat in the first cycle of 49.06 ( pretty skilled category ) . Then in the second cycle of 67.97 ( skilled category ) and the third cycle was 82.5 ( highly skilled category ) . Activities of students in the first cycle meeting I got a score of 41.67 ( category less ) increased to 50 ( category enough ) at a meeting II . Then in the second cycle the meeting I got a score of 62.5 ( both categories ) increased to 75 ( both categories ) in the second cycle II meeting . Later in the first meeting of the third cycle of 83.33 ( excellent category ) increased in the third cycle II meeting at 91.67 ( excellent category ) . Activities of teachers in the first cycle meeting I got a score of 54.17 ( enough categories ) increased to 58.33 ( category enough ) at a meeting II . Then in the second cycle the meeting I got a score of 70.83 ( good category ) increased to 79.16 ( both categories ) in the second cycle II meeting . Later in the first meeting of the third cycle of 87.5 ( excellent category ) increased in the third cycle II meeting at 95.83 ( excellent category ) . Based on the results of the study it can be concluded that the application of the model to improve the skills of fat PAIKEM GEMBROT form of clay material in class IVB SD Negeri 56 Pekanbaru .Thus the research hypothesis proved.Keywords :Model PAIKEM GEMBROT fat , Skills Shaping of clay material .